A size-resolved chemical mass balance (SR-CMB) approach for source apportionment of ambient particulate matter by single element analysis. (15th January 2019) - Dai, Qili; Bi, Xiaohui; Huangfu, Yanqi; Yang, Jiamei; Li, Tingkun; Khan, Jahan Zeb; Song, Congbo; Xu, Jiao; Wu, Jianhui; Zhang, Yufen; Feng, Yinchang
Abstract: The size distribution of a particle population has proven to be of great value in source apportionment studies. Previous studies have reported that particle size distributions in ambient urban air vary with location and time, indicating that the ambient particles are affected by known sources. However, the size distributions of individual chemical species emitted from primary sources have received relatively little attention. This study presents a preliminary real-world investigation of the size distributions of particles emissions from coal-fired power plants, residential coal combustion, biomass burning, vehicles, soil dust and steelworks based on a high size-resolution measurement using an Electrical Low Pressure Impactor. The size profiles of individual chemical elements are found to have a high degree of source specificity, which assists source classification. We subsequently employed a chemical mass balance approach termed size-resolved CMB (SR-CMB), which is based on the use of both physical and chemical information on the high size-resolution measurements of particulate matter. By applying SR-CMB on the measured ambient data, source contributions to ambient particles were successfully obtained when copper (Cu) was chosen as the fitting species. The approach described in this paper enhances the capability of the CMB model and provides a useful tool to validate results of traditional receptor models when a high size-resolution measurement is available. This effort also highlights that the size profiles of sources is of potential concern in the situations when the chemically collinear sources exist. Highlights: Particles emissions from six sources were measured by using ELPI + . Size profiles of Cu have a high degree of source specificity. A size-resolved CMB was successfully employed for source apportionment of PM.